A Journey to the West. Observations on the Chinese Migration to Italy - pedone, valentina (Studi e saggi, 2013)
This volume presents the results of a number of studies about Chinese migration to Italy carried out between 2003 and 2013. The data discussed in the different chapters were collected mostly through ethnographic fieldwork carried out both in China and in Italy. Covered topics include: the organization of Chinese trade activities in Italy, the perception of Italy as a country of migration, identity construction among Italian-born Chinese, language use among Chinese migrants in Italy and literary works written by Chinese in Italy. In addition to the chapters devoted to the discussion of data gathered from fieldwork, an introductory chapter based on a review of the scientific literature is offered in order to provide the reader with a basic background about the characteristics of a migration flow that has lasted nearly a century.